Conservation of tropical birds - Sodhi, Navjot S. (Wiley-Blackwell, 2011)
Conservation of Tropical Birds has been written by four conservation biologists whose expertise spans all the tropical regions of the world. It is the first book to cover all the major issues in tropical bird conservation. Current problems faced by tropical bird conservationists are summarised and potential solutions outlined based on the results of case studies. Birds are key indicators of ecosystem health, and such a well-studied group of organisms, that they provide an excellent lens through which to examine global conservation problems caused by phenomena such as climate change, declines in.